Seasonal Variations of Zooplankton in Nazik Lake (Turkey) - Saler, Serap; Bulut, Hilal; Güneş, Seçil; Alpaslan, Kenan; Karakaya, Gökhan (Fırat University, 2019)
In this study, zooplankton community of Nazik Lake studied seasonally. Zooplankton samples were collected from three different stations with standart hydro-bios plankton net, both horizontally and vertically. In the lake 25 zooplankton species were identified. Zooplankton samples were consisted of 14 Rotifera, 8 Cladocera, and 3 Copepoda, respectively. Rotifera was the dominant group of zooplankton with regard to species numbers and densities